Effectiveness ofIsotonic Pelvic AbductorExercise onKnee Osteoarthritis - Abubakar RudiSoebagyo, Hermilawaty; Idha Handajani, Noor (International Journal of Psychosocial Rehabilitation, 2020)
Background, Osteoarthritis (OA) is the disorder with a high prevalence of sufferers that affects joints in the knees. Abdominal abductor strengthening exercises in quadriceps and hamstring muscle can reduce dynamic loading on the medial side of the knee. Besides that, the addition of isotonic quadriceps femoral muscle and pelvic joint abductor muscles is considered to have effectiveness in reducing pain perception. Objectives: This study aims to know the effect of additional isotonic exercises of femoral quadriceps through pain perception improvement, increase femoral quadriceps strength, and increase the physical function of patients with knee osteoarthritis (OA). Methods: The sample size was 20 knee OA patients. Subjects were randomly divided into the isotonic exercise of femoral quadriceps plus the isotonic exercise of hip abductor group and the isotonic exercise of femoral quadriceps only group. The assessment and measurement were conducted in the pain perception of the Visual Analog Scale (VAS), the strengthening of quadriceps femoral muscle (1 RM), and the functional physic status of the Western Ontario and McMaster Universities (WOMAC) Scale. This analysis was conducted using the Mann-Whitney test with SPSS software. Results: The intervention group improved their perceived pain symptoms, decreased stiffness subscale, and increased physical function subscale of WOMAC (all p<0.05). The femoral quadriceps strength and pain subscales of WOMAC were improved in both groups (p = 0.0001). Conclusions: Isotonic exercise supplementation of hip abductors with isotonic exercise offemoral quadriceps provided additional benefits with respect to the perceived pain symptoms, decreased stiffness, and increased physical function of patients with knee OA after three weeks of treatment.